The current situation of hereditary angioedema patients in Germany: results of an online survey - Magerl, Markus; Martinez-Saguer, Inmaculada; Schauf, Lucia; Pohl, Sven; Brendel, Klaus (Frontiers in Medicine, 2024)
Introduction Hereditary angioedema (HAE) is a rare hereditary disease with an estimated prevalence of approximately 1 in 50,000. Methods An online survey was performed between January and June 2021 on a total of 99 HAE patients (with 92 of them aged 15 years and older and 7 of them being parents of patients under the age of 15 years). They were asked about their current situation, with a focus on the disease. Results The survey results show that HAE has a strong influence on the patients’ quality of life. In particular, the anxiety and uncertainty of not knowing when a swelling attack will occur is considered burdensome by the patients. In addition, there can be physical problems during an attack (depending on its severity) that severely burden and limit patients in their everyday lives. Only one-third of the patients surveyed stated that no or only very minor physical limitations occurred during their most recent swelling attack. Almost three-quarters of all patients receive regular treatment at an HAE center. The patients are mostly satisfied with the therapy and particularly with long-term prophylactics (LTPs). When an LTP was used, the frequency and severity of the swelling attacks, and their duration, were significantly lower and/or shorter than when no LTP was used. Discussion Despite the high level of satisfaction with their current medication, 62% of patients expressed a strong/very strong interest in an oral LTP. In the group of patients already using an LTP, 74% reported a strong/very strong interest in an oral medication for long-term prophylaxis. The simplicity and minimal time involved in LTP use are considered beneficial to patients’ quality of life.